Study of Tissue Cyst Formation Time of Toxoplasma gondii in Mice - M. Hanafiah; Wisnu Nurcahyo; Sumartono S (Jurnal Kedokteran Hewan, 2007)
The purpose of the research was to study a tissue cyst formation time Toxoplasma gondiiexperimentally. A number of 84 mice were divided randomly into four groups. Each group consisted of 21mice. The mice of the group I were infected with 101, II with 102 and III with 10 tachyzoites respectivelyintraperitoneally, whereas the group IV as a control (not infected with tachyzoites). All infected micewere treated with sulfadiazine, 15 mg/mouse per oral diluted in drinking water, for 5 days. On first untiltwenty first day after treatment one mouse of each group was necropsied. Liver, lymph, kidney, lung,heart, brain, or diaphragm muscle were then taken for histological preparations. Data on tissue cystformation time was analysed descriptively. The research revealed that innoculation with tachyzoites 103cyst could be found on day 14th after infection of liver, 102 cyst was found on the 6 day of liver, in day7th in heart and brain on day 10th of after infection, 103 cyst was found on day 4th inheart and brain in day 7thth in liver, day 6 after infection, while in the control dosage there is no formation similar to cyst found.Keywords: cyst, tissue, T. gondii, mice th1